A Study on Value Conflicts and Mental Health of Students at The Higher Secondary Level in Relation to Their Social Maturity - Selvam, S.K. Panneer (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Man is an integrated psychometric unit, whose behaviour is determined by both physical and mental factors. Every one today appears to be tenser than the past either due to lack of understanding and confidence among themselves or because of psychopathic morbidities like parent child relationship, loveless domestic life, broken families, global terrorism and narrow considerations. People can be both humanly pro-social and destructively anti-social as they are not necessarily aware of their values; some may even conflict with conscious values to sustainable development. A child is born in a home where he remains in the constant company of his mother in the formative years of his sustainable development infancy. The impressions and experiences which a child has in these formative years leave permanent and sustainable development to indelible impressions on his mind. sustainable development is at times minimal or immense, at times ridden or open and at times constructive or destructive, any time in making a choice at the cost of another, conflict is a perceived incompatibility of actions and goals that prevents, obstructs interfere, injuries or in some way makes another activity less likely or less effective. Health is a state of being hale, sound or whole some in body and mind. It means that both body and mind are working efficiently and harmoniously.